2022
DOI: 10.1155/2022/5936773
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy and Side Effects of Irinotecan Combined with Nedaplatin versus Paclitaxel Combined with Cisplatin in Neoadjuvant Chemotherapy for Locally Advanced Cervical Cancer and Tumor Marker Analysis: Based on a Retrospective Analysis

Abstract: Objective. A case-control study was adopted to investigate the efficacy and side effects of irinotecan combined with nedaplatin (NP) versus paclitaxel combined with cisplatin for locally advanced cervical cancer (CC) neoadjuvant chemotherapy (NACT) and to analyze the changes in tumor marker levels. Methods. A total of 96 patients with locally advanced CC who were treated from October 2019 to October 2021 were enrolled in our hospital as the research subjects, and their clinical data were collected for retrospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Myelosuppression is a common side effect in uterine cervical neoplasia. [ 36 ] It was observed in 5 studies. [ 24 , 26 , 30 , 31 , 33 ] The combined results revealed a significantly lower incidence of myelosuppression in the experimental group compared to the control group (RR = 0.41, 95% CI: 0.26–0.64, P < .0001, 5 studies, 466 patients).…”
Section: Resultsmentioning
confidence: 99%
“…Myelosuppression is a common side effect in uterine cervical neoplasia. [ 36 ] It was observed in 5 studies. [ 24 , 26 , 30 , 31 , 33 ] The combined results revealed a significantly lower incidence of myelosuppression in the experimental group compared to the control group (RR = 0.41, 95% CI: 0.26–0.64, P < .0001, 5 studies, 466 patients).…”
Section: Resultsmentioning
confidence: 99%
“…Irinotecan is a widely used anti-chemotherapeutic agent and has many known side effects [ 20 ]. Various agents against irinotecan toxicity have been established in previous studies [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%